Degradation of ochratoxin A by proteases and by a crude enzyme of aspergillus niger - Abrunhosa, Luís (2006)
Ochratoxin A is a mycotoxin present in food commodities as cereals, wine, coffee, figs, dried vine fruits or beer and in feeds for animals. The enhancement of its conversion into ochratoxin a is considered to be a way to reduce its presence in the body and, therefore, its toxicity. In this paper we report the ability of several commercial proteases to hydrolyze ochratoxin A into ochratoxin a in different amounts. After an incubation period of 25 h., a significant hydrolytic activity at pH 7.5 for Protease A (87.3%), and for Pancreatin (43.4%) was detected. At pH 3.0, a weak hydrolytic activity was detected for Prolyve PAC (3%). None of the other commercial enzymes tested were able to hydrolyze ochratoxin A in the tested conditions. Also, the isolation of an enzyme extract from an Aspergillus niger strain with very strong ochratoxin A hydrolytic activity at pH 7.5 (99.8%) is reported. This activity is similar to the activity detected in Protease A. Data about the inhibition effect of ethylenediaminetetraacetic acid and phenylmethanesulfonyl fluoride on the involved hydrolytic enzymes showed that enzymes involved in ochratoxin A hydrolysis are metalloproteins.